CALCULATION OF COMPRESSED COMPOSITE ADHESIVE JOINT ELEMENTS WITH CONCRETE AND STEEL - , Л. І., О. Г. (Municipal economy of cities. Series: «Economy science», 2013)
The article describes methods of calculation of the bearing capacity of composite elements in which the joint work of steel and concrete is provided through bonding. We compare experimental results with theoretical calculations.